What is hidden behind the indicators of ethno-linguistic fragmentation? - Kelly Labart (Fondation pour les études et recherches sur le développement international (FERDI), 2010)
Ethno-linguistic fragmentation has become an unavoidable factor to consider when studying the determinants of growth. In their article of 1997, Easterly and Levine inaugurated the argument that a fragmented countries' ethnic structure, measured by the ethno-linguistic fragmentation index ELF, negatively influences countries' growth. Since this research, further analyses have either validated or challenged the method used by Easterly and Levine to describe ethnic diversity as well as the results they emphasized. The present research provides consequently an overview of the indicators used by the literature to describe and measure ethno-linguistic fragmentation and the argument put forward by the various authors to support the one or the other indicator. It also challenges the exogenous character of the main ethno-linguistic fragmentation indexes usually assumed in the studies analyzing the link between ethnic fragmentation and economic performance. Having a look at the correlations between exogenous characteristics such as the country's surface, the population density and these main indicators, the article provides potential instrumental variables to be used to control for endogeneity of ethno-linguistic fragmentation index when estimating the impact of ethnic fragmentation on economic performance.
Keywords: J11; J15; 330